MODERN VISION OF DEVELOPMENT FACTORS OF PROTEIN-ENERGY MALNUTRITION SYNDROME IN PATIENTS, RECEIVING PERITONEAL DIALYSIS - Lesovoy, V.; Andonieva, N.; Dubovik, M.; Huts, E.; Grushka, M. (Ukrainian Journal of Nephrology and Dialysis, 2017)
Patients who have end-stage chronic kidney disease (СKD) and who receive substitutive peritoneal dialysis (PD) therapy, often have complication such as protein-energy malnutrition syndrome (PEMS). Important prognostic value is given to nutritional disorders as they increase prior disease development, complicate its correction, influence survival rate of patients of this category. Purpose: to explore prevalence of protein-energy malnutrition syndrome in PD patients and define factors of its development. Materials and methods: 67 PD patients were examined. Evaluation of nutritional status in patients under investigation was made using development of complex methodology that includes 5 specifications – body mass index (BMI), triceps skinfold, arm circumference – biceps, floating albumin and seraalbumin, absolute number of lymphocyte. Results. PEMS was found in 35,8% of patients, 29,8% had mild case and 6% had moderate case with mixed form domination. 26,8% of PD patients had average high or high transport characteristics of abdominal membrane that provided increased protein loss through abdominal membrane on PD. It was determined that with the growth of С-reactive protein (CRP) level nutritional disorders increased. In our research chronic inflammation syndrome was found in 16,3% of cases. Besides, protein loss was growing fast after another dialysis peritonitis. Expressed deficit of daily consumption of protein was registered in 29,2% of patients. Conclusion. Our researches analysis allowed us to define that risk factors of formation of protein metabolism disorders in PD patients are low protein consumption, connection with nutritional deficiency syndrome, system inflammatory reaction, protein loss with dialysis fluid having high transport characteristics of abdominal membrane and repeated dialysis peritonitis.